Mechanical properties and residual stresses in multi pass AISI 304 to AISI 1018 steel welds by SMAW and GTAW - Shridhar; Prabhat Kumar Janapareddy; G B Veeresh Kumar; Santosh Kumar Sahu; Ali El-Rayyes; Jayant Giri; Balkeshwar Singh (Scientific Reports)
Abstract Welding is a highly reliable, efficient, and widely used technique for joining metallic structures. In this study, AISI 1018 Mild Steel (MS) and Stainless Steel (SS) AISI 304 were joined using Shielded Metal Arc Welding (SMAW) and Gas Tungsten Arc Welding (GTAW) multipass welding methods. Post-Weld Heat Treatment (PWHT) was performed on the weldments using an induction furnace to analyse the effects of PWHT on microstructural variations, mechanical characteristics and residual stresses of dissimilar weld joints. The results revealed that PWHT improved the mechanical properties of the weld and substantially reduced residual stresses by ~ 48.5% in both SMAW and GTAW weld regions. Additionally, PWHT enhanced impact toughness, with increases of 17.3% for SMAW weldments and 21.4% for GTAW weldments. The weld area exhibited the highest hardness values across all weldments; however, a slight reduction in tensile strength was observed after PWHT due to material softening effects.